IMPROVING PHYSICAL FITNESS OF ELEMENTARY SCHOOL STUDENTS THROUGH KIDS' ATHLETICS GAME PRACTICES: - Aygün, Cihan; Çakır-Atabek, Hayriye (International Online Journal of Education and Teaching, 2023)
Kids’ athletics game practices (KAGP) could be used by physical education teachers during their lessons to keep a large number of children physically active at the same time by playing the athletics. This study aimed to investigate the effects of 4-week KAGP on some physical fitness variables in children, and, to compare these affects between sexes. The study was conducted on 3rd-grade students randomly selected from a primary school. The volunteers exercised the KAGP for 4-weeks, two days per week. The KAGP (formula one, sprint/hurdles shuttle relay, forward squat jumps, and backward overhead throwing), involved straight running, running with changing direction, rolling movement, hurdling, jumping and throwing. Pre-test and post-test measurements were taken for counter movement jump (CMJ), backward overhead medicine ball (BOMB) throwing, agility (Illinois test), flexibility (sit-and-reach), and 30m sprint. Following the 4-week KAGP, the CMJ (Pre:16.04±3.33 cm; Post:18.46±2.90 cm) significantly increased, and the 30m sprint time (Pre:6.94±0.61 sec; Post:6.74±0.57 sec) significantly shorten only in girls (p = .003 and p = .008, respectively). The agility significantly improved (Pre:24.03±2.00 sec; Post:23.26±1.83 sec; p = .01) and the BOMB throwing distance significantly increased (Pre: 3.80±0.97 m; 4.45±1.18 m; p = .001) considering the overall data. Significant difference between boys and girls was observed for CMJ performance. It has been observed that games structured according to the purpose have positive effects on the strength and agility properties of children. KAGP can be used as a tool to increase physical activity and improve physical fitness in children at primary level.